A new energy battery insulation protection UV tape and preparation method thereof

By coating soy protein isolate on the montmorillonite surface of battery insulated UV tape and grafting hydroxymethyl L-tyrosine, combined with the polymerization of modified Malayan anhydride, the problems of uneven curing and insufficient moisture resistance of UV tape are solved, and better insulation and mechanical properties are achieved.

CN119119878BActive Publication Date: 2025-02-28KUNSHAN BYE MACROMOLECULE MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411590680.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Battery insulated UV tape cannot cure ultraviolet due to the blue film being light-transmitted, and the fast curing speed leads to uneven curing, affecting the quality of the battery, and insufficient moisture-proof performance and cohesive strength, affecting the insulation protection effect.

Method used

By coating soy protein isolate on the surface of montmorillonite and grafting hydroxymethyl L-tyrosine to form a Schiff alkali structure, the modified montmorillonite is dispersed in the modified Malayan anhydride, and after ultraviolet curing, the modified montmorillonite is uniformly dispersed in the UV glue layer, improving insulation and moisture resistance.

Benefits of technology

It realizes uniform curing of UV tape, improves insulation and moisture resistance, enhances the protection effect of the battery, and improves the mechanical properties and cohesive strength of UV tape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a new energy battery insulation protection UV tape and a preparation method thereof, which belongs to the technical field of battery UV tape processing, and comprises the following steps: mixing a matrix resin, a modified polymerization monomer, a composite filler, a tackifying resin, an ultraviolet light delayed curing agent, a photobase generating agent, a photoinitiator, an antioxidant, and a solvent, stirring to obtain a UV glue; applying the UV glue to the surface of a substrate blue film, drying to obtain an adhesive layer, and laminating a release film on the surface of the adhesive layer to obtain a UV tape. Soy protein isolate is complexed with metal impurities such as iron, chromium, calcium, magnesium, and sodium in montmorillonite to avoid falling off; the UV tape includes a photobase generating agent, a photoinitiator, and an ultraviolet light delayed curing agent for coordinated use, triggering the preliminary curing of the UV glue, and then laminating the battery surface, so as to achieve a fixing effect within 1-2 hours, and avoid the UV tape curing speed being fast, resulting in uneven curing of the UV tape on the battery, and a short operating time, which affects the battery quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of UV tape processing for batteries, and in particular to an insulating protective UV tape for new energy batteries and a preparation method thereof. Background Art

[0002] UV glue, also known as ultraviolet light-curing glue, is a photoinitiator or photosensitizer in UV light-curing glue that absorbs ultraviolet light under ultraviolet light to produce active free radicals or cations, initiating monomer polymerization and cross-linking chemical reactions, so that the adhesive is converted from liquid to solid within seconds. UV glue can be cured only by using light energy instead of heat, and does not require an additional heating source. It has the advantages of low energy consumption, no solvent, and low VOC emissions. It has little impact on the environment and only requires a small amount of radiation energy to excite the photoinitiator to initiate photopolymerization / curing reaction. The system has a low curing temperature and can be applied to heat-sensitive substrates. The product has excellent performance and is widely used in the field of new energy batteries.

[0003] The battery insulating UV tape includes blue film, UV glue and release film, which is attached to the surface of the new energy battery. Since the blue film is not light-transmissive and cannot be exposed to ultraviolet light, the battery insulating UV tape cannot be UV-cured. In addition, the UV tape cures quickly after being exposed to ultraviolet light, resulting in uneven curing of the UV tape on the battery and a short operating time, which affects the quality of the battery. In addition, the moisture-proof performance and cohesive strength of the battery insulating UV tape affect the protective effect of the battery insulating UV glue on the battery. Summary of the invention

[0004] The invention aims to provide a new energy battery insulation protection UV adhesive tape and a preparation method thereof: soybean protein isolate is coated on the surface of montmorillonite, and the hydroxyl and carboxyl groups contained in the soybean protein isolate can be complexed with metal impurities such as iron, chromium, calcium, magnesium, sodium and the like in the montmorillonite to avoid falling into the UV adhesive layer, which makes the UV adhesive easy to conduct electricity; hydroxymethyl L-tyrosine is grafted on the surface of the montmorillonite coated with the soybean protein isolate, and the formed Schiff base structure has good mildew resistance; modified montmorillonite is dispersed in modified maleopimaric anhydride, and after ultraviolet light curing, the modified maleopimaric anhydride is polymerized, so that the modified montmorillonite is uniformly dispersed in the UV adhesive layer, thereby improving the insulation of the UV adhesive layer; a polymerizable monomer is grafted on the surface of amino-treated nano-aluminum hydroxide, and after ultraviolet delayed curing, the nano-aluminum hydroxide is uniformly dispersed in the UV adhesive layer, thereby providing good moisture resistance.

[0005] The technical problem to be solved by the present invention is as follows: since the blue film is opaque and cannot be irradiated by ultraviolet rays, the battery insulating UV tape cannot be cured, and the UV tape cures quickly after being irradiated by ultraviolet light, resulting in uneven curing of the UV tape on the battery and a short operating time, which affects the battery quality, and the moisture-proof performance and cohesive strength of the battery insulating UV tape affect the protective effect of the battery insulating UV adhesive on the battery.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a new energy battery insulation protection UV tape comprises the following steps:

[0008] S1. Mix and stir the base resin, modified polymer monomer, composite filler, tackifying resin, ultraviolet light delayed curing agent, photobase generator, photoinitiator, antioxidant and solvent to obtain UV glue.

[0009] S2. Apply UV glue on the surface of the blue film of the substrate, dry it at 80-100°C for 5-6 minutes to obtain an adhesive layer, and attach a release film to the surface of the adhesive layer to obtain a UV tape.

[0010] Furthermore, the matrix resin is selected from any one of polyacrylate, polyurethane, ethylene-vinyl acetate copolymer, epoxy acrylate, and glycidyl ether type epoxy resin E51.

[0011] Furthermore, the tackifying resin is selected from any one of α-terpene resin, β-terpene resin and C5 petroleum resin.

[0012] Furthermore, the UV delayed curing agent is selected from UV delayed curing agent T1647, industrial grade, Shanghai Tianzhibao New Material Technology Co., Ltd.

[0013] Furthermore, the photobase generator is selected from sodium tetraphenylborate.

[0014] Furthermore, the photoinitiator is selected from any one of 2-isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and trimethylbenzoyl-diphenylphosphine oxide.

[0015] Furthermore, the antioxidant is selected from any one of tea polyphenols, vitamin E, naringin, and butylated hydroxyanisole.

[0016] Furthermore, the solvent is any one of ethyl acetate, acetone, butanone or toluene.

[0017] Furthermore, the mass ratio of base resin, modified polymer monomer, composite filler, tackifying resin, UV delayed curing agent, photobase generator, photoinitiator, antioxidant and solvent is (45-55):(10-15):(5-10):(1-2):(0.5-0.8):(0.3-0.4):(1-2):(0.2-0.4):(40-50).

[0018] Furthermore, the substrate blue film is selected from polyethylene terephthalate blue film, with a thickness of 48-52 μm and a TTV (difference between maximum thickness and minimum thickness) of 2-80 μm.

[0019] Furthermore, the release film is selected from polyethylene terephthalate release film and has a thickness of 48-52 μm.

[0020] Furthermore, the thickness of the adhesive layer is 48-52 μm.

[0021] Furthermore, the composite filler is prepared by reacting maleopimaric anhydride with allyl chloride and then mixing with modified montmorillonite, and is specifically prepared by the following steps:

[0022] A1. Add maleopimaric anhydride to deionized water, stir evenly, add 10% by mass sodium hydroxide aqueous solution until the aqueous solution becomes a dark yellow clear solution, distill under reduced pressure, and dry in an oven at 40°C for 10 min to obtain sodium maleopimarate;

[0023] Sodium maleopimarate, methyl trioctyl ammonium chloride and hydroquinone are added to N,N-dimethylformamide as polymerization inhibitors, stirred evenly, allyl chloride is added, stirred for 30 minutes, placed in a microwave reactor, reacted for 4 hours at a microwave reaction temperature of 55°C and a microwave power of 400 W, n-hexane is added for extraction and the n-hexane layer is collected, solids are precipitated after the n-hexane layer is allowed to stand for 24 hours, the filtrate is collected by filtration, and the filtrate is distilled under reduced pressure to obtain modified sodium maleopimarate.

[0024] A2. The modified montmorillonite and modified maleopimaric anhydride were stirred at 25°C for 30 minutes to obtain a composite filler.

[0025] Furthermore, in the above-mentioned reaction process A1, maleopimaric anhydride is mixed with a sodium hydroxide aqueous solution, and the carboxyl group in the maleopimaric anhydride can combine with the sodium ions in the sodium hydroxide aqueous solution to form sodium maleopimaric acid, thereby giving the maleopimaric anhydride reaction activity; methyltrioctyl ammonium chloride is used as a catalyst and hydroquinone is used as an inhibitor, so that the carboxyl structure contained in the sodium maleopimaric acid can undergo a substitution reaction with the chlorine atom of allyl chloride, and the formed modified maleopimaric anhydride contains three photopolymerizable double bonds. Under the action of ultraviolet light, the modified maleopimaric anhydride can be cured in the UV adhesive layer to form a polymer, which can improve the adhesion strength, thermal stability and flexibility of the UV adhesive layer.

[0026] Furthermore, during the above-mentioned A2 reaction process, the polar functional groups contained in the soybean protein isolate and hydroxymethyl L-tyrosine on the surface of the modified montmorillonite have good adhesion and can be combined with the ester group on the modified maleopimaric anhydride through hydrogen bonds, so that the modified montmorillonite is dispersed in the modified maleopimaric anhydride. After ultraviolet light curing, accompanied by the polymerization of the modified maleopimaric anhydride, the modified montmorillonite is evenly dispersed in the UV adhesive layer, thereby improving the insulation of the UV adhesive layer.

[0027] Furthermore, in step A1, the ratio of maleopimaric anhydride to deionized water is (2.5-2.9) g:(10-20) mL.

[0028] Furthermore, in step A1, the mass ratio of sodium maleopimarate, methyl trioctyl ammonium chloride, hydroquinone, N,N-dimethylformamide and allyl chloride is (8-12):(0.3-0.7):(0.01-0.03):(25-35):(9-9.8).

[0029] Furthermore, in step A2, the ratio of modified montmorillonite to modified maleopimaric anhydride is (0.4-0.5) g:(8-12) mL.

[0030] Further, maleopimaric anhydride is specifically prepared by the following steps:

[0031] Add rosin and maleic anhydride to glacial acetic acid, stir evenly, place in a microwave reactor, stir and react for 25-35 minutes at a temperature of 110-130°C and a microwave power of 380-420W, cool to room temperature, filter to obtain a crude product, and purify the crude product by recrystallization with glacial acetic acid to obtain maleopimaric anhydride.

[0032] The method comprises the following steps: in glacial acetic acid, the rosin is converted into L-pimaric acid through microwave heating reaction, and the L-pimaric acid is further reacted with maleic anhydride through diene addition reaction to generate maleopimaric anhydride.

[0033] Furthermore, the dosage ratio of rosin, maleic anhydride and glacial acetic acid is (2-3) g:(1.4-1.8) g:(35-45) mL.

[0034] Furthermore, the modified montmorillonite is prepared by mixing soy protein isolate with montmorillonite and then reacting with hydroxymethyl L-tyrosine, specifically by the following steps:

[0035] B1. Add soy protein isolate to deionized water, stir evenly, add 40% by mass sodium hydroxide aqueous solution to adjust the pH to 9.3, stir at 50°C for 30 minutes, add montmorillonite, and continue stirring for 20 minutes to obtain a mixture.

[0036] B2. The mixture and hydroxymethyl L-tyrosine were added to deionized water, and a 40% by mass sodium hydroxide aqueous solution was added, and the mixture was stirred and reacted at 55° C. for 10 min. The mixture was filtered and washed with deionized water for 3 times to obtain modified montmorillonite.

[0037] Furthermore, during the above B1 reaction, the polar groups hydroxyl and carboxyl contained in the soy protein isolate can be chemically bonded to the hydroxyl groups on the surface of montmorillonite, and the soy protein isolate has excellent adhesion, so that the soy protein isolate is coated on the surface of montmorillonite.

[0038] Furthermore, during the above-mentioned B2 reaction process, in the mixture, the amino groups contained in the montmorillonite coated with soy protein isolate on the surface can react with the hydroxymethyl groups of hydroxymethyl L-tyrosine, so that the hydroxymethyl L-tyrosine is grafted on the surface of the mixture. The formed Schiff base structure has good anti-mildew activity and can improve the anti-mildew performance of the new energy battery insulation protection UV tape.

[0039] Furthermore, in step B1, the ratio of soy protein isolate, deionized water and montmorillonite is (4-6) g: (40-50) mL: (0.5-0.9) g.

[0040] Furthermore, in step B2, the ratio of the mixture, hydroxymethyl L-tyrosine, deionized water, and sodium hydroxide aqueous solution is (1-2) g: (0.3-0.7) g: (8-12) mL: (1-3) mL.

[0041] Furthermore, the particle size of montmorillonite is 0.1-2 μm and the purity is 84-86%.

[0042] Further, hydroxymethyl L-tyrosine is specifically prepared by the following steps:

[0043] L-tyrosine, a 36-38% formaldehyde aqueous solution and deionized water are mixed, stirred evenly, heated to 25-35°C, 1 g of a 35-45% sodium hydroxide aqueous solution is added, stirred at 400-500 rpm for 4-6 hours, and freeze-dried in a -20°C freeze dryer to remove some residual water and formaldehyde to obtain hydroxymethyl L-tyrosine.

[0044] Furthermore, the mass ratio of L-tyrosine, formaldehyde aqueous solution, deionized water, and sodium hydroxide aqueous solution is (2-3):(3-4):(8-12):(0.5-1.5).

[0045] Furthermore, the modified polymer monomer is prepared by reacting 1,5-dihydroxynaphthalene, epichlorohydrin and acrylic acid, and then mixing with amino-treated nano-aluminum hydroxide, and is specifically prepared by the following steps:

[0046] C1. Add 1,5-dihydroxynaphthalene and epichlorohydrin to acetone, reflux at 60°C for 2h, add 40% by mass aqueous sodium hydroxide solution, continue stirring and reacting for 24h, filter, wash with ether 3 times, and wash with deionized water 3 times to obtain epoxidized 1,5-dihydroxynaphthalene, add epoxidized 1,5-dihydroxynaphthalene to epichlorohydrin, stir at 80°C until the solid is dissolved, add acrylic acid, stir and react at 50°C for 10h, place in a mixture of methanol and ether for recrystallization, take out the precipitate, and obtain a polymerizable monomer.

[0047] C2. Add amino nano-aluminum hydroxide and polymerizable monomers to ethanol, stir evenly, then add 36% by mass aqueous hydrochloric acid solution, stir and react at 50°C for 15 minutes, filter, wash with deionized water 3 times, dry in an oven at 60°C for 10 minutes, and obtain a modified polymerizable monomer.

[0048] Furthermore, in the above C1 reaction process, in the organic solvent acetone, the hydroxyl group of 1,5-dihydroxynaphthalene reacts with the chlorine atom of epichlorohydrin to obtain epoxidized 1,5-dihydroxynaphthalene; the epoxidized 1,5-dihydroxynaphthalene is dissolved in epichlorohydrin, and at 80°C, the epoxidized 1,5-dihydroxynaphthalene undergoes a ring-opening reaction with the carboxyl group of acrylic acid, and the acrylic acid monomer is grafted onto the epoxidized 1,5-dihydroxynaphthalene to obtain a polymerizable monomer.

[0049] Furthermore, in the above C2 reaction process, the amino group carried by the aminated nano-aluminum hydroxide polymerizable monomer can be chemically bonded to the hydroxyl group generated by the ring opening in the polymerizable monomer, so that the polymerizable monomer acts on the surface of the aminated nano-aluminum hydroxide to obtain a modified polymerizable monomer.

[0050] Furthermore, in step C1, the ratio of 1,5-dihydroxynaphthalene, epichlorohydrin, acetone, and sodium hydroxide aqueous solution is (1-3) g: (15-25) mL: (10-20) mL: (0.1-0.3) mL.

[0051] Furthermore, in step C1, the ratio of epoxidized 1,5-dihydroxynaphthalene, epichlorohydrin, and acrylic acid is (0.5-1.5) g: (15-25) mL: (1-3) g.

[0052] Furthermore, in step C2, the ratio of the amount of amino-modified nano-aluminum hydroxide, polymerizable monomer, ethanol, and hydrochloric acid aqueous solution is (1-1.4) g: (8-12) g: (45-55) mL: (0.2-0.4) mL.

[0053] Further, the amination nano aluminum hydroxide is specifically prepared by the following steps:

[0054] Add nano aluminum hydroxide to deionized water, stir evenly to obtain a dispersion, add KH550 to ethanol and deionized water, stir for 20 minutes, add to the dispersion, stir and react at 80°C for 2 hours, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80°C for 10 minutes to obtain amino nano aluminum hydroxide.

[0055] Furthermore, the dosage ratio of nano aluminum hydroxide to deionized water is (1-2) g: (25-35) mL.

[0056] Furthermore, the dosage ratio of KH550, ethanol, and deionized water is (0.1-0.3) g: (1-3) mL: (16-20) mL.

[0057] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) In the technical solution of the present invention, montmorillonite can effectively prevent the passage of electric current, thereby reducing battery discharge and leakage, and can still maintain stable insulation performance under high electric field strength, is not prone to breakdown, and has excellent insulation performance; soy protein isolate is coated on the surface of montmorillonite, and the hydroxyl and carboxyl groups contained in the soy protein isolate can complex with metal impurities such as iron, chromium, calcium, magnesium, and sodium in the montmorillonite to avoid falling into the UV adhesive layer, causing the UV adhesive to be easily conductive and affecting the insulation performance of the UV tape.

[0059] (2) In the technical solution of the present invention, hydroxymethyl L-tyrosine is grafted onto the surface of montmorillonite coated with soy protein isolate, and the formed Schiff base structure has good mildew resistance, which can improve the mildew resistance of the new energy battery insulation protection UV tape. Soy protein isolate and hydroxymethyl L-tyrosine can undergo cross-linking reaction on the surface of montmorillonite to form a dense cross-linked network structure on the surface of montmorillonite, which can reduce the penetration of water molecules and prevent the montmorillonite from swelling after absorbing water, causing the size of the material to change and affecting the insulation performance. In addition, the formed cross-linked network structure has good mechanical properties, which enhances the mechanical properties of the battery UV tape.

[0060] (3) In the technical solution of the present invention, maleopimaric anhydride reacts with allyl chloride to form modified maleopimaric anhydride containing three photopolymerizable double bonds. Under the action of ultraviolet light, the modified maleopimaric anhydride can be cured in the UV adhesive layer to form a polymer, which can improve the adhesion strength and flexibility of the UV adhesive layer; the modified montmorillonite is dispersed in the modified maleopimaric anhydride. After ultraviolet light curing, the modified maleopimaric anhydride is polymerized, so that the modified montmorillonite is uniformly dispersed in the UV adhesive layer, thereby improving the insulation of the UV adhesive layer. In addition, the modified montmorillonite can increase the crosslinking density of the modified maleopimaric anhydride polymer, thereby further enhancing the cohesive strength of the UV adhesive layer.

[0061] (4) In the technical scheme of the present invention, 1,5-dihydroxynaphthalene, epichlorohydrin and acrylic acid react to obtain a polymerizable monomer. After UV curing, the polymerizable monomer can form a strong covalent bond with the acrylic copolymer of the UV adhesive layer matrix, and the polymerizable monomer is introduced into the UV adhesive layer matrix. The polymerizable monomer contains a thermally stable aromatic structure, which increases the decomposition temperature of the UV adhesive layer, thereby increasing the thermal stability of the UV tape; the polymerizable monomer is grafted onto the surface of amino-treated nano-aluminum hydroxide. On the one hand, the nano-aluminum hydroxide has acidic buffering capacity, which reduces the hydrolysis rate of the UV resin and improves the moisture-proof performance of the UV adhesive layer. On the other hand, the composite acts on the surface of the amino-treated nano-aluminum hydroxide. After UV delayed curing, the nano-aluminum hydroxide is evenly dispersed in the UV adhesive layer, providing better moisture-proof properties.

[0062] (5) In the technical solution of the present invention, the raw materials of UV glue include a photobase generator, a photoinitiator and an ultraviolet light delayed curing agent, which are used in coordination. After ultraviolet light irradiation, the UV glue is initially cured and then bonded to the battery surface. The fixing effect is achieved within 1-2 hours, and the bonding effect reaches the best state after 24 hours. This avoids the UV tape curing at a fast speed after ultraviolet light irradiation, resulting in uneven curing of the UV tape on the battery, short operating time, and affecting the battery quality. In addition, by adding modified polymer monomers and composite fillers, the UV tape is provided with better mechanical properties, cohesive strength, mildew resistance, moisture resistance and insulation properties. DETAILED DESCRIPTION

[0063] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] The raw materials used in the embodiments of the present invention are as follows:

[0065] Allyl chloride, hydroquinone, N,N-dimethylformamide, n-hexane (analytical grade, Aladdin Biochemical Technology Co., Ltd.); maleic anhydride (purity of 99.5%, Jinan Jinhao Chemical Co., Ltd.); L-tyrosine (purity of 99%, Henan Zhengxing Food Additive Co., Ltd.); nano-aluminum hydroxide (particle size of 50-100nm, purchased from Tianjin Guangfu Technology Development Co., Ltd.); soy protein isolate (purity of 95.5%, Zhongtian Shanghai Biotechnology Co., Ltd.); allyl chloride (analytical grade, Guangdong Wengjiang Chemical Reagent Co., Ltd.); 1,5-dihydroxynaphthalene (purity of 98%, Hubei Biaoyue Biotechnology Development Co., Ltd.); epichlorohydrin (Kunshan Yalong Trading Co., Ltd.); acrylic acid (purity of 99.5%, Jinan Jiao Chemical Co., Ltd.).

[0066] The UV delayed curing agent is selected from UV delayed curing agent T1647, industrial grade, Shanghai Tianzhibao New Material Technology Co., Ltd.

[0067] Maleopimaric anhydride is specifically prepared by the following steps:

[0068] 2.5 g of rosin and 1.6 g of maleic anhydride were added to 40 mL of glacial acetic acid, stirred evenly, placed in a microwave reactor, stirred and reacted for 30 min at a temperature of 120° C. and a microwave power of 400 W, cooled to room temperature, filtered to obtain a crude product, and the crude product was recrystallized and purified with glacial acetic acid to obtain maleopimaric anhydride.

[0069] Sodium maleopimarate is specifically prepared by the following steps:

[0070] 2.7 g of maleopimaric anhydride was added to 15 mL of deionized water, stirred evenly, and a 10% by mass sodium hydroxide aqueous solution was added until the aqueous solution became a dark yellow clear solution. The solution was distilled under reduced pressure and dried in an oven at 40°C for 10 min to obtain sodium maleopimaric acid.

[0071] Hydroxymethyl L-tyrosine is specifically prepared by the following steps:

[0072] 2.5 g of L-tyrosine, 3.4 g of 37% formaldehyde aqueous solution and 10 g of deionized water were mixed, stirred evenly, heated to 30°C, 1 g of 40% sodium hydroxide aqueous solution was added, stirred at 450 rpm for 5 h, and freeze-dried in a -20°C freeze dryer to remove some residual water and formaldehyde to obtain hydroxymethyl L-tyrosine.

[0073] The amination nano aluminum hydroxide is prepared by the following steps:

[0074] Add 1.5 g of nano aluminum hydroxide to 30 mL of deionized water, stir evenly to obtain a dispersion, add 0.2 g of KH550 to 2 mL of ethanol and 18 mL of deionized water, stir for 20 min, add to the dispersion, stir and react at 80 ° C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80 ° C for 10 min to obtain amino nano aluminum hydroxide.

[0075] Embodiment 1:

[0076] The composite filler is specifically prepared by the following steps:

[0077] A1. Add 5 g of soy protein isolate to 45 mL of deionized water, stir evenly, add 40% by mass sodium hydroxide aqueous solution to adjust the pH to 9.3, stir at 50°C for 30 min, add 0.7 g of montmorillonite, and continue stirring for 20 min to obtain a mixture.

[0078] A2. Add 1.5 g of the mixture and 0.5 g of hydroxymethyl L-tyrosine to 10 mL of deionized water, add 2 mL of a 40% sodium hydroxide aqueous solution, stir and react at 55°C for 10 min, filter, and wash with deionized water three times to obtain modified montmorillonite.

[0079] A3. 10 g of sodium maleopimarate, 0.5 g of methyl trioctyl ammonium chloride and 0.02 g of hydroquinone as a polymerization inhibitor were added to 30 g of N,N-dimethylformamide, and stirred evenly. 9.4 g of allyl chloride was added and stirred for 30 min. The mixture was placed in a microwave reactor and reacted for 4 h at a microwave reaction temperature of 55 ° C and a microwave power of 400 W. 50 mL of n-hexane was added for extraction and the n-hexane layer was collected. After the n-hexane layer was allowed to stand for 24 h, solids precipitated. The filtrate was collected by filtration and the filtrate was distilled under reduced pressure to obtain modified sodium maleopimarate. 0.5 g of modified montmorillonite and 10 mL of modified maleopimaric anhydride were stirred at 25 ° C for 30 min to obtain a composite filler.

[0080] Comparative Example 1 The difference between this comparative example and Example 1 is that the mixture is replaced by montmorillonite, and the remaining steps and raw materials are the same as Example 1.

[0081] A1. Add 1.5 g of montmorillonite and 0.5 g of hydroxymethyl L-tyrosine to 10 mL of deionized water, add 2 mL of 40% sodium hydroxide aqueous solution, stir and react at 55°C for 10 min, filter, and wash with deionized water three times to obtain modified montmorillonite.

[0082] A2. 10 g of sodium maleopimarate, 0.5 g of methyl trioctyl ammonium chloride and 0.02 g of hydroquinone as a polymerization inhibitor were added to 30 g of N,N-dimethylformamide, and stirred evenly. 9.4 g of allyl chloride was added and stirred for 30 min. The mixture was placed in a microwave reactor and reacted for 4 h at a microwave reaction temperature of 55 ° C and a microwave power of 400 W. 50 mL of n-hexane was added for extraction and the n-hexane layer was collected. After the n-hexane layer was allowed to stand for 24 h, solids precipitated. The filtrate was collected by filtration and the filtrate was distilled under reduced pressure to obtain modified sodium maleopimarate. 0.5 g of modified montmorillonite and 10 mL of modified maleopimaric anhydride were stirred at 25 ° C for 30 min to obtain a composite filler.

[0083] Comparative Example 2 The difference between this comparative example and Example 1 is that hydroxymethyl L-tyrosine is not added, and the remaining steps and raw materials are the same as Example 1.

[0084] A1. Add 5 g of soy protein isolate to 45 mL of deionized water, stir evenly, add 40% by mass sodium hydroxide aqueous solution to adjust the pH to 9.3, stir at 50°C for 30 min, add 0.7 g of montmorillonite, and continue stirring for 20 min to obtain a mixture.

[0085] A2. 10 g of sodium maleopimarate, 0.5 g of methyl trioctyl ammonium chloride and 0.02 g of hydroquinone as a polymerization inhibitor were added to 30 g of N,N-dimethylformamide, and stirred evenly. 9.4 g of allyl chloride was added and stirred for 30 min. The mixture was placed in a microwave reactor and reacted for 4 h at a microwave reaction temperature of 55°C and a microwave power of 400 W. 50 mL of n-hexane was added for extraction and the n-hexane layer was collected. After the n-hexane layer was allowed to stand for 24 h, solids precipitated. The filtrate was collected by filtration and the filtrate was distilled under reduced pressure to obtain modified sodium maleopimarate. 0.5 g of the mixture and 10 mL of modified maleopimaric anhydride were stirred at 25°C for 30 min to obtain a composite filler.

[0086] Comparative Example 3 The difference between this comparative example and Example 1 is that modified sodium maleopimarate is not added, and the remaining steps and raw materials are the same as those in Example 1.

[0087] A1. Add 5 g of soy protein isolate to 45 mL of deionized water, stir evenly, add 40% by mass sodium hydroxide aqueous solution to adjust the pH to 9.3, stir at 50°C for 30 min, add 0.7 g of montmorillonite, and continue stirring for 20 min to obtain a mixture.

[0088] A2. Add 1.5 g of the mixture and 0.5 g of hydroxymethyl L-tyrosine into 10 mL of deionized water, add 2 mL of a 40% sodium hydroxide aqueous solution, stir and react at 55°C for 10 min, filter, and wash with deionized water three times to obtain a composite filler.

[0089] Embodiment 2:

[0090] The modified polymer monomer is specifically prepared by the following steps:

[0091] B1. Add 2 g of 1,5-dihydroxynaphthalene and 20 mL of epichlorohydrin to 15 mL of acetone, reflux at 60°C for 2 h, add 0.2 mL of 40% by mass sodium hydroxide aqueous solution, continue stirring and reacting for 24 h, filter, wash with ether 3 times, and wash with deionized water 3 times to obtain epoxidized 1,5-dihydroxynaphthalene, take 1 g of epoxidized 1,5-dihydroxynaphthalene and add it to 20 mL of epichlorohydrin, stir at 80°C until the solid is dissolved, add 2 g of acrylic acid, stir and react at 50°C for 10 h, place in a mixture of 10 g of methanol and 10 g of ether for recrystallization, take out the precipitate, and obtain a polymerizable monomer.

[0092] B2. Add 1.2g of amino-modified nano-aluminum hydroxide and 10g of polymerizable monomer into 50mL of ethanol, stir evenly, then add 0.3mL of 36% hydrochloric acid aqueous solution, stir and react at 50°C for 15min, filter, wash with deionized water 3 times, dry in an oven at 60°C for 10min, and obtain a modified polymerizable monomer.

[0093] Comparative Example 4 The difference between this comparative example and Example 2 is that the amino-treated nano-aluminum hydroxide is replaced by nano-aluminum hydroxide, and the remaining steps and raw materials are the same as those in Example 2.

[0094] B1. Add 2 g of 1,5-dihydroxynaphthalene and 20 mL of epichlorohydrin to 15 mL of acetone, reflux at 60°C for 2 h, add 0.2 mL of 40% by mass sodium hydroxide aqueous solution, continue stirring and reacting for 24 h, filter, wash with ether 3 times, and wash with deionized water 3 times to obtain epoxidized 1,5-dihydroxynaphthalene, take 1 g of epoxidized 1,5-dihydroxynaphthalene and add it to 20 mL of epichlorohydrin, stir at 80°C until the solid is dissolved, add 2 g of acrylic acid, stir and react at 50°C for 10 h, place in a mixture of 10 g of methanol and 10 g of ether for recrystallization, take out the precipitate, and obtain a polymerizable monomer.

[0095] B2. Add 1.2g of nano-aluminum hydroxide and 10g of polymerizable monomer into 50mL of ethanol, stir evenly, then add 0.3mL of 36% hydrochloric acid aqueous solution, stir and react at 50°C for 15min, filter, wash with deionized water 3 times, dry in an oven at 60°C for 10min to obtain a modified polymerizable monomer.

[0096] Comparative Example 5 The difference between this comparative example and Example 2 is that no amino-treated nano-aluminum hydroxide is added, and the remaining steps and raw materials are the same as those in Example 2.

[0097] Add 2 g of 1,5-dihydroxynaphthalene and 20 mL of epichlorohydrin to 15 mL of acetone, reflux at 60°C for 2 h, add 0.2 mL of 40% by mass sodium hydroxide aqueous solution, continue stirring and reacting for 24 h, filter, wash with ether 3 times, and wash with deionized water 3 times to obtain epoxidized 1,5-dihydroxynaphthalene. Take 1 g of epoxidized 1,5-dihydroxynaphthalene and add it to 20 mL of epichlorohydrin, stir at 80°C until the solid is dissolved, add 2 g of acrylic acid, stir and react at 50°C for 10 h, place it in a mixture of 10 g of methanol and 10 g of ether for recrystallization, take out the precipitate, and obtain a modified polymerizable monomer.

[0098] Embodiment 3:

[0099] A method for preparing a new energy battery insulation protection UV tape comprises the following steps:

[0100] S1. 45g of polyurethane, 10g of the modified polymerized monomer prepared in Example 2, 5g of the composite filler prepared in Example 1, 1g of α-terpene resin, 0.5g of UV delayed curing agent T1647, 0.3g of sodium tetraphenylborate, 1g of 2-isopropylthioxanthone, 0.2g of butylated hydroxyanisole, and 40g of ethyl acetate were mixed and stirred to obtain UV glue.

[0101] S2. Apply UV glue on the surface of the blue film of the substrate, dry it in an oven at 90°C for 7 minutes to obtain an adhesive layer, and attach a release film to the surface of the adhesive layer to obtain a UV tape.

[0102] The substrate blue film is selected from polyethylene terephthalate blue film and has a thickness of 50 μm.

[0103] The release film is selected from polyethylene terephthalate release film and has a thickness of 50 μm.

[0104] The thickness of the adhesive layer was 50 μm.

[0105] Embodiment 4:

[0106] A method for preparing a new energy battery insulation protection UV tape comprises the following steps:

[0107] S1. 50g of polyacrylate, 13g of the modified polymerization monomer prepared in Example 2, 8g of the composite filler prepared in Example 1, 1.5g of β-terpene resin, 0.6g of UV delayed curing agent T1647, 0.35g of sodium tetraphenylborate, 1.5g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 0.3g of tea polyphenols, and 45g of acetone were mixed and stirred to obtain UV glue.

[0108] S2. Apply UV glue on the surface of the blue film of the substrate, dry it in an oven at 90°C for 7 minutes to obtain an adhesive layer, and attach a release film to the surface of the adhesive layer to obtain a UV tape.

[0109] The substrate blue film is selected from polyethylene terephthalate blue film and has a thickness of 50 μm.

[0110] The release film is selected from polyethylene terephthalate release film and has a thickness of 50 μm.

[0111] The thickness of the adhesive layer was 50 μm.

[0112] Embodiment 5:

[0113] A method for preparing a new energy battery insulation protection UV tape comprises the following steps:

[0114] S1. 55g of ethylene-vinyl acetate copolymer, 15g of the modified polymerization monomer prepared in Example 2, 10g of the composite filler prepared in Example 1, 2g of C5 petroleum resin, 0.8g of UV delayed curing agent T1647, 0.4g of sodium tetraphenylborate, 2g of trimethylbenzoyl-diphenylphosphine oxide, 0.4g of vitamin E, and 50g of butanone were mixed and stirred to obtain UV glue.

[0115] S2. Apply UV glue on the surface of the blue film of the substrate, dry it in an oven at 90°C for 7 minutes to obtain an adhesive layer, and attach a release film to the surface of the adhesive layer to obtain a UV tape.

[0116] The substrate blue film is selected from polyethylene terephthalate blue film and has a thickness of 50 μm.

[0117] The release film is selected from polyethylene terephthalate release film and has a thickness of 50 μm.

[0118] The thickness of the adhesive layer was 50 μm.

[0119] Comparative Example 6 The difference between this comparative example and Example 4 is that the composite filler prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are the same as Example 4.

[0120] Comparative Example 7 The difference between this comparative example and Example 4 is that the composite filler prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are the same as Example 4.

[0121] Comparative Example 8 The difference between this comparative example and Example 4 is that the composite filler prepared in Example 1 is replaced by the material prepared in Comparative Example 3, and the remaining steps are the same as Example 4.

[0122] Comparative Example 9 The difference between this comparative example and Example 4 is that the modified polymerized monomer prepared in Example 2 is replaced by the substance prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.

[0123] Comparative Example 10 The difference between this comparative example and Example 4 is that the modified polymerized monomer prepared in Example 2 is replaced by the substance prepared in Comparative Example 5, and the remaining steps are the same as Example 4.

[0124] The performance of the UV tapes prepared in Examples 3-5 and Comparative Examples 6-10 is now tested;

[0125] Curing time test: 0.5 g of the prepared UV glue was weighed on a glass slide and placed under a UV lamp and the curing time was recorded until the UV glue had no fluidity. This period of time was recorded as the curing time. The curing time of the present invention was measured to be 1-2 h.

[0126] Mechanical properties test: tear off the release film on the UV tape, expose it to ultraviolet light with a wavelength of 365nm and an energy of 5000mJ / cm2 for 10s, stick one side of the exposed tape on the battery aluminum plate, press and bond it with a pressure of 0.1MPa for 24h, and then test the shear strength according to the national standard GB / T7124-2008. Tensile strength test: test the tensile strength according to GB13022-1991.

[0127] Adhesion performance test: Adhesion performance is tested according to GB / T9286-1998 standard.

[0128] Insulation test: Use the DC resistance test method. According to the IEC61109 standard, the test voltage should be 500V and the test time should be 5 minutes to test the insulation resistance value of the UV tape.

[0129] Anti-mildew and moisture-proof properties: After 10 g of the UV glue prepared above was placed at a temperature of 32° C. and a humidity of 80% for 24 h, a UV tape was prepared according to step S2 of Example 3-5, and the shear strength was tested.

[0130] The test results are shown in Table 1 below:

[0131]

[0132] It can be seen from the data in Table 1 that in Comparative Example 6, the composite filler prepared by replacing the mixture with montmorillonite is added to the UV tape, and its insulation and mildew resistance decrease. This may be because the hydroxyl and carboxyl groups contained in the soy protein isolate can be complexed with metal impurities such as iron, chromium, calcium, magnesium, and sodium in the montmorillonite to avoid falling into the UV adhesive layer, causing the UV adhesive to be easily conductive and affecting the insulation performance of the UV tape. The Schiff base structure formed by hydroxymethyl L-tyrosine and soy protein isolate has good mildew resistance, but the montmorillonite surface lacks soy protein isolate, and this effect cannot be achieved, so the insulation and mildew resistance decrease;

[0133] Comparative Example 7: The composite filler prepared without adding hydroxymethyl L-tyrosine was added to the UV tape, and its insulation and mechanical properties decreased. This may be because the soy protein isolate and hydroxymethyl L-tyrosine can form a dense cross-linked network structure on the surface of montmorillonite, which can reduce the penetration of water molecules and prevent the montmorillonite from swelling after absorbing water, causing the size of the material to change and affecting the insulation performance. In the absence of hydroxymethyl L-tyrosine, this effect cannot be achieved, so the insulation and mechanical properties are reduced;

[0134] Comparative Example 8: When the composite filler prepared without modified maleopimaric anhydride was added to the UV tape, its shear strength and insulation performance decreased. This may be because the modified maleopimaric anhydride can be cured in the UV adhesive layer to form a polymer, which can improve the adhesion strength and flexibility of the UV adhesive layer, and the modified montmorillonite is uniformly dispersed in the UV adhesive layer with the polymerization of the modified maleopimaric anhydride, thereby improving the insulation of the UV adhesive layer. Without the modified maleopimaric anhydride, this effect cannot be achieved. Therefore, with the polymerization of the modified maleopimaric anhydride, the modified montmorillonite is uniformly dispersed in the UV adhesive layer, thereby improving the insulation of the UV adhesive layer, which decreases.

[0135] In Comparative Example 9, the modified polymerized monomer prepared from nano-aluminum hydroxide is added to the UV tape instead of the amino-aluminum hydroxide, and its moisture-proof performance is reduced. This may be because the polymerizable monomer is grafted onto the surface of the amino-aluminum hydroxide, and after UV delayed curing, the nano-aluminum hydroxide is evenly dispersed in the UV adhesive layer, providing better moisture-proof performance. However, the surface of nano-aluminum hydroxide does have reactive functional groups, which cannot achieve this effect, and thus the moisture-proof performance is reduced.

[0136] In Comparative Example 10, the modified polymer monomer prepared without adding amino-aluminum nano-hydroxide was added to the UV tape, and its moisture-proof performance decreased. This may be because nano-aluminum hydroxide has acidic buffering capacity, which reduces the hydrolysis rate of the UV resin and improves the moisture-proof performance of the UV adhesive layer. The modified polymer monomer lacks moisture-proof amino-aluminum nano-hydroxide and cannot achieve this effect, so the moisture-proof performance decreases.

[0137] The data in Table 1 show that the UV tapes prepared in Examples 3-5 meet the test performance requirements, while the UV tapes prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the UV tapes prepared in the present invention have good mechanical properties, cohesive strength, mildew resistance, moisture resistance and insulation properties.

[0138] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0139] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a new energy battery insulation protection UV tape, characterized in that: The following steps are involved: S1. Mixing the base resin, the modified polymer monomer, the composite filler, the tackifying resin, the UV delayed curing agent, the photobase generating agent, the photoinitiator, the antioxidant, and the solvent, and stirring to obtain a UV glue; S2. Apply UV glue on the surface of the blue film of the substrate, dry it at 80-100°C for 5-6 minutes to obtain an adhesive layer, and attach a release film to the surface of the adhesive layer to obtain a UV tape; The composite filler is prepared by reacting maleopimaric anhydride with allyl chloride and then mixing with modified montmorillonite; The modified montmorillonite is prepared by mixing soy protein isolate with montmorillonite and reacting with hydroxymethyl L-tyrosine; The modified polymer monomer is prepared by reacting 1,5-dihydroxynaphthalene, epichlorohydrin and acrylic acid and then mixing with amino-treated nano aluminum hydroxide.

2. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The montmorillonite particle size is 0.1-2 μm and the purity is 84-86%.

3. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The maleopimaric anhydride is specifically prepared by the following steps: Add rosin and maleic anhydride to glacial acetic acid, stir evenly, place in a microwave reactor, stir and react for 25-35 minutes at a temperature of 110-130°C and a microwave power of 380-420W, cool to room temperature, filter to obtain a crude product, and purify the crude product by recrystallization with glacial acetic acid to obtain maleopimaric anhydride.

4. The method for preparing a new energy battery insulation protection UV tape according to claim 3, characterized in that: The dosage ratio of the rosin, maleic anhydride and glacial acetic acid is (2-3) g: (1.4-1.8) g: (35-45) mL.

5. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The hydroxymethyl L-tyrosine is specifically prepared by the following steps: L-tyrosine, a 36-38% formaldehyde aqueous solution and deionized water are mixed, stirred evenly, heated to 25-35°C, a 35-45% sodium hydroxide aqueous solution is added, stirred at a rate of 400-500 rpm for 4-6 hours, and freeze-dried in a -20°C freeze dryer to remove some residual water and formaldehyde to obtain hydroxymethyl L-tyrosine.

6. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The ultraviolet light delayed curing agent is selected from ultraviolet delayed curing agent T1647, industrial grade; the photobase generator is selected from sodium tetraphenylborate.

7. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The photoinitiator is selected from any one of 2-isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and trimethylbenzoyl-diphenylphosphine oxide.

8. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The tackifying resin is selected from any one of α-terpene resin, β-terpene resin and C5 petroleum resin.

9. The method for preparing a new energy battery insulation protection UV tape according to claim 1, characterized in that: The solvent is any one of ethyl acetate, acetone, butanone or toluene; the antioxidant is any one of tea polyphenols, vitamin E, naringin and butylated hydroxyanisole.

10. The UV tape prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Special adhesive used for high-temperature resistant electronic circuit pad board and added with organic modified montmorillonite

    CN106244097A

  • Insulating adhesive film with low dielectric loss and preparation method and application thereof

    CN114181652A